Role of ultrasound in detection of metastatic neck nodes in patients with oral cancer - P Sureshkannan; Vijayprabhu; Reena John (Wolters Kluwer Medknow Publications, 2011)
Introduction: Head and neck cancer is one of the most physically and emotionally devastating cancers and often leaves the patient disabled and disfigured. The presence of cervical metastasis is one of the factorsthat influence the outcome of the patients. Cervical lymph node metastasis plays an essential role in the treatment and prognosis of head and neck cancer patients. The assessment of the cervical lymph node status still remains an unsolved problem. We conducted a study to compare the diagnostic accuracy of clinical palpation and ultrasonogram (USG) in the detection of metastatic cervical nodes from oral squamous cell carcinoma patients. Materials and Methods: Ten patients (age range, 45-63 years; mean age, 54 years) with squamous cell carcinoma in the head and neck region underwent clinical palpation and USG. The results of each modality were analyzed for sensitivity, specificity, positi ve predictive value, negative predictive value and accuracy. Pathologic analysis of the surgical resection served as the reference standard. Results: USG yielded a sensitivity, specificity, positive, negative predictive value and accuracy as 85.7%, 90%, 92.3%, 81.8% and 87.5% whereas clinical palpation yielded a sensitivity, specificity, positive, negative predictive value and accuracy as 68.7%, 87.5%, 91.6%, 58.3% and 75%. Conclusion: USG is a reliable and valuable tool for metastatic lymph node screening in head and neck cancer patients. It is a cheap, noninvasive, easy-to-handle and cost-effective diagnostic method. USG performed better than clinical palpation in detecting cervical metastatic nodes.